Meaning of childhood adolescence youth transition in people with chronic kidney disease - Flor Neyfy Botina Muñoz; LUIS ALEXANDER LOVERA MONTILLA; Luz Angela Argote Oviedo; Jaime Manuel Restrepo Restrepo (Universidad de Alicante, 2018)
Introduction: The transition to youth in children and adolescents with chronic kidney disease (CKD) brings many changes that nursing professionals must incorporate in care protocols for health promotion and prevention of kidney disease. Objective: To deepen, in people on dialysis therapy, the meaning of have lived the transition childhood, adolescence, youth with CKD. Methodology: Qualitative study, following Grounded Theory in data. Nine participants aged between 18 and 24 years. The data collection was carried out through in-depth interviews and under the criteria of credibility, auditability and transferability. Findings: Through codification data, theoretical sampling and the constant comparative method, emerged three categories: 1) Childhood: Stage of normality, without recognition of latent kidney disease, 2) Adolescence: an awakening stage when a health issue is confirmed, uncertainty about the life project and final acceptance of dialysis therapy as a way of survival and 3) Youth: transplantation, a hope for a life change. Conclusion: The transition from childhood to youth in people with CKD, is a journey that begins in childhood, in disregard of the health problem; continues into adolescence with uncertainty for the construction of a life project given the dependence on dialysis therapy; and finally, in youth, with entry into kidney transplant program, it is transformed into a hope for a life change.